(3GdGMUGA hJUeje GdJLGQH aj GdHMhK GdfaSjI hGdJQHhjI hGdGLJeGYjI (B/s - (3GdTQHjfj, RcQjG CMeOs ((3GdbGgQI(B: s (3ecJHI GdGfLdh GdeUQjI(B, s, 2007)
(3jVe GdJLQjH hGdJUejeGJ GdJLQjHjI, eHGOF GMUGFjI ddJUejeGJ GdJLQjHjI, GdJUeje GdJLQjHj HeYGdLI hGMOI hGdJUeje GdJLQjHj HeYGdLJjf, GdJUeje GdJLQjHj HCcKQ ef eYGdLJjf ddbjGSGJ GdeSJbdI, GdJUeje GdYGedj KfGFj GdEJLGg ddbjGSGJ GdeSJbdI, GdJUeje GdJLQjHj HCcKQ ef eYGdLJjf, GdJUeje GdeNJdW, GdJUeje GdYGedjf KdGKj GdEJLGg, GdJMdjd GdEMUGFj GdeGhQGFjs
(3HjHjdhZQGajG(B: (3U U(B.534-540s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdJLGQH(B- (3Ydhes; (3JUeje GdJLGQHs